Why Another School? The Doctrinal History and Reasons for the Formation of Immanuel Lutheran High School, College, and Seminary - Tiefel, Mark (My University, 2009)
My paper analyzes the split between two major synods within Lutheranism and how this led to the formation of the Church of the Lutheran Confession (CLC) and Immanuel Lutheran High School, College, and Seminary (ILC), located in Eau Claire, Wisconsin. The two synods that split were the Lutheran Church-Missouri Synod (LCMS) and the Wisconsin Evangelical Lutheran Synod (WELS). The WELS is a more conservative synod and they cut ties with the LCMS because of its change from conservative to liberal viewpoints on certain doctrines. The Evangelical Lutheran Synod (ELS), also referred to as the Norwegian Synod, is another synod that is involved in this period of history but since the ELS is in confessional agreement with the WELS it is grouped with the WELS. The CLC, also a conservative synod, formed as a result of separation from the LCMS, WELS, and ELS over disagreements in doctrine and, as a result of this separation, ILC was formed as a school of the CLC. Therefore it is essential to look both at the broad perspective of liberalism vs. conservatism as it applies to the LCMS and the WELS and also the strife within the conservative synods that led to the formation of the CLC. This history, both broad and specific, describes the doctrinal reasons for the formation of ILC and why this institution is so important to its members.
Keywords: Immanuel Lutheran High School, College, & Seminary (Eau Claire, Wis.); Lutheran Church--Doctrines--History.; Lutheran Church--Wisconsin--History.; Church of the Lutheran Confession.